2020
DOI: 10.24246/j.js.2020.v10.i1.p22-33
|View full text |Cite
|
Sign up to set email alerts
|

Permasalahan Budaya Membaca di Indonesia (Studi Pustaka Tentang Problematika & Solusinya)

Abstract: Reading is one of the language skills that must be mastered by every student, the ability to read becomes one of the mandatory components in the national education curriculum. However, assessment programs of various international institutions and the Ministry of Education & Culture show that students in Indonesia are still low in their reading ability, in this case reading comprehension skills. For this reason, through this literature study, the problems and solutions are examined based on various library … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
41
1
67

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(109 citation statements)
references
References 2 publications
0
41
1
67
Order By: Relevance
“…It can be proven from reading and literacy of PIRLS (Progress in International Reading Literacy Study), that informed more than 95% of Indonesian students in grade IV elementary schools were only able to study in the middle level. Furthermore the results of the PIRLS study (Progress in International Reading Literacy Study), Indonesia ranked 45th out of 48 participating countries with a score of 428 from an average score of 500 (Tahmidaten & Krismanto, 2020;IEA 2017;Kobakhidze, 2016). These data above can be indicated that education in Indonesian country was still be worried about or at a low level on the international achievement index.…”
Section: Introductionmentioning
confidence: 90%
“…It can be proven from reading and literacy of PIRLS (Progress in International Reading Literacy Study), that informed more than 95% of Indonesian students in grade IV elementary schools were only able to study in the middle level. Furthermore the results of the PIRLS study (Progress in International Reading Literacy Study), Indonesia ranked 45th out of 48 participating countries with a score of 428 from an average score of 500 (Tahmidaten & Krismanto, 2020;IEA 2017;Kobakhidze, 2016). These data above can be indicated that education in Indonesian country was still be worried about or at a low level on the international achievement index.…”
Section: Introductionmentioning
confidence: 90%
“…The reading culture developed in schools should be strengthened through the library. However, the school library's inadequate facilities and infrastructure and services sometimes become one of the obstacles to developing students' reading interests and abilities (Tahmidaten & Krismanto, 2020). Therefore, TBM is one of the means that should be able to cover these shortcomings.…”
Section: Development and Management Of Tbm Widuri Pandanmentioning
confidence: 99%
“…According to Tahmidaten and Krismanto (2020), when discussing the role of libraries, it must be seen from four (4) sides, namely: 1) facilities, 2) administration management, 3) human resources managers, and 4) library utilisation programs to support the reading movement. (School literacy).…”
Section: Development and Management Of Tbm Widuri Pandanmentioning
confidence: 99%
“…The main adjustment experienced by master students is the adaptation with the nature of academic reading activities (Alghail & Mahfoodh, 2016). In the context of Indonesia, the different number of academic reading text in undergraduate compared to master degree might cause shock for master students since Indonesia has a low reading culture (Tahmidaten & Krismanto, 2020). In other words, students are not accustomed to having reading habits.…”
Section: Introductionmentioning
confidence: 99%